Gulf Elites’ dependence on international press in times of crisis : the US-Iran crisis 2019-2020 - Ziani, Abdulkarim; Elareshi, Mokhtar; Chaudhary, Shubhda; Alsridi, Hatem (Penerbit Universiti Kebangsaan Malaysia, 2022)
International press coverage is often considered a legitimate source of informed opinion, especially during a political conflict such as the US-Iran crisis in 2019-2020. The international press coverage needs an in-depth understanding of such socio-political relationships to understand direct media effects and media dependability. Most studies have examined the intersection of international relations with communication and media studies and failed to consider the effects of emotional, cognitive and behavioural media on other non-state actors involved in the conflict. This study attempts to identify the degree to which the Gulf Elites – powerful non-state actors – depend and prefer the international press (newspapers) for following news coverage of the crisis, their news coverage professionalism, and news sources. An online survey was conducted with a snowball sampling technique which resulted in more than 200 Gulf Elites (following Al-Din Hassan’s classification) in five Gulf countries: Bahrain, Saudi Arabia, Oman, UAE, and Kuwait. The research indicated that, overall, these newspapers were followed/read to some extent, with a preference for accessing them online, confirming the ease of online accessibility in the region. The two UK newspapers were highly preferred compared to the two US and French newspapers. However, the news coverage of the crisis was described as lacking professionalism, and respondents showed a lack of interest in following such coverage, highlighting the emergence of Pan-Arab media.